The Use of Digital Storytelling in Teaching Listening Comprehension - Juvrianto Chrissunday Jakob; Haryanto Atmowardoyo; Sukardi Weda (ELT Worldwide: Journal of English Language Teaching, 2018)
ABSTRACTThis study focuses on finding out whether or not the use of Digital Storytelling (DST) develops the students’ listening comprehension and to find out the students’ learning interest towards the use of DST. The research employed QUAN – Qual model. The writers gathered the data by using listening comprehension tests and open ended questions. The finding of the study revealed that the students’ result of post-test for experimental group was higher than the students’ result in post-test for control group. The difference of the students’ score was statistically significant; the probability value is smaller than significant level (0.000 < 0.05). The result was H1 is accepted and H0 is rejected. While, the open ended question result showed that students agree that learning English by using digital story is a good supporting media since they have used it for about four weeks in the process of teaching and learning.